PERAN KETELADANAN GURU PKN DALAM MEMBENTUK KARAKTER DISIPLIN PADA SISWA KELAS IX SMP ISLAM AL FATTAHIYYAH BOYOLANGU TULUNGAGUNG - Fadilla Tri Wahyuni; Muhamad Abdul Roziq Asrori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of the role of Civic Education (PKn) teachers as role models in shaping students' disciplinary character within the school environment. Discipline is one of the essential character values that should be instilled in students to encourage compliance with rules and responsibilities. The purpose of this study is to describe the role of PKn teachers' exemplary behavior in developing disciplinary character among ninth-grade junior high school students, identify the forms of exemplary behavior demonstrated by teachers, and examine their impact on students' disciplinary attitudes.This study employed a qualitative approach using a descriptive research design. The research was conducted at SMP Islam Al-Fattahiyyah Boyolangu Tulungagung. Data were collected through interviews, observations, and documentation. The research participants included PKn teachers, ninth-grade students, and relevant school personnel. The findings reveal that the exemplary behavior of PKn teachers plays a significant role in fostering students' disciplinary character. The forms of exemplary behavior demonstrated by teachers include punctuality, regular attendance, compliance with school regulations, and consistency in carrying out duties and responsibilities. These positive examples contribute to improved student discipline, reflected in greater adherence to school rules, better participation in learning activities, and increased responsibility in completing academic tasks. Therefore, the exemplary conduct of PKn teachers serves as an important factor in strengthening students' disciplinary character.